INTERVENTIONS FOR PSYCHOEMOTIONAL MANAGEMENT FOR COVID-19 PATIENTS: A SCOPING REVIEW - González Ortiz, Angélica; Calderón Jeraldo, Jeniffer; Cea Nettig, Ximena (Chilean Journal of Primary Care and Family Health, 2022)
Objective: To characterize the psycho emotional interventions in the research approach of people and families with COVID-19 infection. Methods: A scoping Review of works published between 2019 and 2021 in Spanish and English, on PubMed, Web of Science, Virtual Health Library and Embase was carried out. Pieces of Research that addressed the psycho emotional management of patients with COVID-19 and their families were selected. The MMAT tool was used to assess the methodological quality of the studies, applied by two independent evaluators. Results: 13 articles were included, most of them were randomized controlled trials. Performing psychological interventions in COVID-19 patients was found to be effective. Interventions were observed from 2 to 3 weeks; reporting benefits in patients from the first week of application. On the other hand, digital communication channels (telephone interventions, chat, video recordings, online video calls, etc.) are as beneficial as face-to-face assistance. Conclusion: Performed early and in a timely manner, through different modalities, interventions to preserve or improve mental health must be an essential part of clinical care in patients with COVID-19. Actions that address the mental health crisis associated with the condition should be promoted, with long-term approaches. In this field, new pieces of Research that integrate a representative number of patients, in order to ensure the effectiveness of the measures, as well as those that demonstrate the potential of outpatient interventions, are also required.